Modeling e-commerce adoption factors among Gen-Z in a developing country: the case of Ghana - Pobee, Frederick (Marketing & Menedzsment, 2021)
THE AIM OF THE PAPER This study aims to investigate the factors that influence e-commerce adoption among Gen Z in a developing country. METHODOLOGY A cross-sectional data were gathered from 522 Gen Z population in the most populous and industrious regions in Ghana. Partial Least Square- Structural Equation Modelling (PLS-SEM) was employed to assess the hypothesized relationships. MOST IMPORTANT RESULTS The findings indicate that effort expectancy, facilitating conditions, information quality, and system quality significantly affect the behavioral intention to adopt e-commerce among gen Z in Ghana. However, performance expectancy, social influence, and service quality had an insignificant effect on behavioral intention. This study is one of the few that have integrated the UTAUT model with DeLone and McLean IS success model to investigate e-commerce adoption. In a developing country context, and to the best of the author’s knowledge, this is the first research to investigate the e-commerce adoption of a particular generation (Gen Z) in Ghana. RECOMMENDATIONS The paper concludes that the ease of using online shopping applications, the readiness and availability of support service for online purchases, information quality, and the efficiency and reliability of e-commerce systems significantly influence gen Z adoption of e-commerce. As a result, e-vendors and website business designers should ensure that the design and layout of e-commerce websites must be easy for consumers to navigate, provide a 24-hour consumer support system, and ensure efficiency and reliability of the e-commerce system.